PERAN KEPALA MADRASAH DALAM MENINGKATKAN MUTU PENDIDIKAN DI MADRASAH IBTIDAIYAH DAMPIT KABUPATEN MALANG - Rismawatul Hasanah; Rosichin Mansur; Fita Mustafida (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2021)
This study discusses the role of madrasah principals in improving the quality of education at Madrasah Ibtidaiyah (MI) Nasruddin Dampit Malang Regency. MI Nasruddin is a madrasa under the auspices of the Islamic boarding school foundation. In addition, MI Nasruddin is supported by friendly leadership, a comfortable environment, students who excel in both academic and non-academic fields, and are able to compete in the tightness of education in Dampit District. Research focus; how is the quality of education? What is the role of the madrasa principal? what are the supporting and inhibiting factors in improving the quality of education? The purpose of this study is to describe the quality of education, the role of the madrasa principal, the supporting and inhibiting factors in improving the quality at MI Nasruddin Dampit. The research was conducted at MI Nasruddin Dampit, Malang Regency. This type of research uses a qualitative approach with the type of case study. Collecting data using observation, interviews and documentation. The data sources used are primary and secondary. Test the validity of the data, namely the credibility test. Data analysis uses data reduction, data presentation and conclusion drawing. The conclusion of this study is that the madrasah principal has a good role in improving the quality of education at MI Nasruddin, this can be seen from student achievement, comfortable environment, good cooperation with the community and teacher staff.Keywords: The Headmasters Roles, educational quality improvement